The wolf [large type] - Ward, J. R., 1969- (Ward, J. R., 1969- Black dagger brotherhood. Prison camp ;, 2022)
"Things get steamy when Lucan, a wolven forced into bartering drug deals for the infamous Prison Colony, meets Rio, the second in command for the shadowy Caldwell supplier, Mozart. After a deal goes awry, a wolf with piercing golden eyes swoops in to save Rio from certain death. As shocking truths unfurl, Rio is uncertain of who to trust and what to believe--but with her life on the line, true love rears its head and growls in the face of danger."--